Effect of insulation with bubble wrap and an absorbent pad on heat loss in anaesthetised cats. Issue 6 (1st November 2020) - Sakata, H; Walsh, V; Chambers, JP; Bridges, J; Sano, H
ABSTRACT: Aims: To evaluate the efficacy of insulating the limbs and thorax of cats with a combination of bubble wrap and an absorbent, plastic-lined pad in reducing heat loss during ovariohysterectomy. Methods: A preliminary study was performed to compare heat loss of 1 L bags of Hartmann's solution heated to 38°C which were either wrapped in two layers of bubble wrap and an absorbent pad (n = 6) or were unwrapped (n = 6). Bags were allowed to cool in a temperature-controlled room and the temperature of the bags was measured every 10 minutes for 60 minutes. The clinical study, included 16 intact female cats undergoing ovariohysterectomy. The cats were premedicated with I/M morphine and either medetomidine or dexmedetomidine, and anaesthesia was induced with I/V propofol and maintained with isoflurane in 100% oxygen. Cats were randomly assigned to either the treatment group (n = 8) whose limbs and thorax wrapped with two layers of bubble wrap and an absorbent pad immediately after induction, or the control group (n = 8) which were unwrapped. Body temperature (measured with an oesophageal temperature probe), heart rate, respiratory rate, mean arterial pressure and partial pressure of end-tidal CO2 were recorded immediately after induction ( T start ), before surgery started ( T surgery ), and at the end of isoflurane administration ( T end ). The times from T end to extubation, from T end to when the cat could maintain sternal recumbency and from T end to when the cat was able to stand, were also recorded. Results: In the preliminary study of heat loss by fluid bags, the mean temperature at 60 minutes was higher in wrapped bags (35.4 (SD 0.2)°C) compared to unwrapped bags (33.0 (SD 0.3)°C; p < 0.01). For cats undergoing ovariohysterectomy, mean body temperature of wrapped cats was higher than that of unwrapped cats both at T surgery (36.0 (SE 0.3) vs. 34.5 (SE 0.3)°C; p = 0.001) and at T end (37.2 (SE 0.5) vs. 36.0 (SE 0.5)°C; p = 0.01). Wrapped cats regained the ability to stand more rapidly that unwrapped cats (26.4 (SE 5.8) vs. 47.0 (SE 5.8) minutes p = 0.01). Conclusions: Wrapping the limbs and thorax of cats undergoing ovariohysterectomy in a combination of bubble wrap and absorbent pads reduced heat loss, which in turn improved recovery time from general anaesthesia. Clinical relevance: This inexpensive and practical method may reduce perioperative hypothermia, in cats undergoing abdominal surgery.